2003
DOI: 10.1677/joe.0.1780159
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone responsiveness in N-Tera-2 cells

Abstract: N-TERA-2 cl/D1 (NT2) cells, a human embryonal cell line with characteristics of central nervous system precursor cells, were utilised to study thyroid hormone action during early neuronal growth and differentiation. Undifferentiated NT2 cells expressed mRNAs encoding thyroid hormone receptors (TRs) 1, 2 and 1, iodothyronine deiodinases types 2 (D2) and 3 (D3) (which act as the pre-receptor regulators), and the thyroid hormoneresponsive genes myelin basic protein (MBP) and neuroendocrine specific protein A (NSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Because T 4 was provided for only a short time, the interpretation was that the duration of T 4 treatment was not sufficient to produce a significant reduction in cellular levels of NSP-A mRNA. However, Chan et al (2003) have recently reported that NSP-A expression is not directly sensitive to TH in N-Tera-2 cells, indicating that NSP-A may not be directly regulated by TH. If maternal hypothyroidism increases NSP-A expression indirectly, and NSP-A is not directly regulated by TH, then our present results indicate that PCBs produce effects on the fetal brain by exerting direct TH-like effects as well as by inducing low maternal TH.…”
Section: Discussionmentioning
confidence: 99%
“…Because T 4 was provided for only a short time, the interpretation was that the duration of T 4 treatment was not sufficient to produce a significant reduction in cellular levels of NSP-A mRNA. However, Chan et al (2003) have recently reported that NSP-A expression is not directly sensitive to TH in N-Tera-2 cells, indicating that NSP-A may not be directly regulated by TH. If maternal hypothyroidism increases NSP-A expression indirectly, and NSP-A is not directly regulated by TH, then our present results indicate that PCBs produce effects on the fetal brain by exerting direct TH-like effects as well as by inducing low maternal TH.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which MND alters TR isoform expression are at present unclear but our results suggest that fetal hypothyroxinaemia may play a role. T 3 treatment of several CNS cell types in vitro results in an increase in TRβ1 mRNA expression (Lebel et al 1993; Chan et al 2003 b ), with little effect on mRNAs encoding the TRα isoforms. This is likely to be mediated via direct T 3 regulation at the two thyroid hormone response elements described in the promoter regions of the TRβ (c‐erbAβ) gene (Sakurai et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were passaged and split 1:4 twice weekly, and cultured at 37°C and 5% CO 2 . Differentiation of NT2 precursor cells to terminally differentiated neurons with retinoic acid (RA) treatment was conducted based on methods previously described (Pleasure et al 1992; Chan et al 2003). Charcoal‐stripped FBS (First Link Ltd, Birmingham, UK), which is virtually devoid of THs, was used to create a T3‐depleted environment.…”
Section: Methodsmentioning
confidence: 99%
“…Since NT2 cells were unable to tolerate 5 weeks in culture with media supplemented with charcoal‐stripped FBS alone, differentiation experiments were performed in media containing 2% of normal FBS with 8% of charcoal‐stripped FBS (combination media) with the addition of 10 n m T3 (T3‐replete) and without T3 (T3‐depleted) along with 10 μ m RA (Sigma‐Aldrich). We had previously shown that the dose of 10 n m T3 was optimal in the induction of T3‐responsive gene expression in NT2 cells (Chan et al 2003).…”
Section: Methodsmentioning
confidence: 99%